Prognostic implications of thyroid hormones in acute aortic dissection: mediating roles of renal function and coagulation - Shen, Xuejun; Wu, Shiwan; Yan, Jingyi; Yan, Hongle; Zhou, Shuyi; Weng, Huozhen; Yang, Shengli; Li, Weiping (Frontiers in Endocrinology, 2024)
Background Thyroid hormones significantly influence cardiovascular pathophysiology, yet their prognostic role in acute aortic dissection (AAD) remains inadequately explored. This study assesses the prognostic value of thyroid hormone levels in AAD, focusing on the mediating roles of renal function and coagulation. Methods We included 964 AAD patients in this retrospective cohort study. Utilizing logistic regression, restricted cubic splines, and causal mediation analysis, we investigated the association between thyroid hormones and in-hospital mortality and major adverse cardiovascular events (MACEs). Results In AAD patients overall, an increase of one standard deviation in FT4 levels was associated with a 31.9% increased risk of MACEs (OR 1.319; 95% CI 1.098-1.584) and a 36.1% increase in in-hospital mortality (OR 1.361; 95% CI 1.095-1.690). Conversely, a higher FT3/FT4 ratio was correlated with a 20.2% reduction in risk of MACEs (OR 0.798; 95% CI 0.637-0.999). This correlation was statistically significant predominantly in Type A AAD, while it did not hold statistical significance in Type B AAD. Key renal and coagulation biomarkers, including blood urea nitrogen, creatinine, cystatin C, prothrombin time ratio, prothrombin time, and prothrombin time international normalized ratio, were identified as significant mediators in the interplay between thyroid hormones and MACEs. The FT3/FT4 ratio exerted its prognostic influence primarily through the mediation of renal functions and coagulation, while FT4 levels predominantly impacted outcomes via a partial mediation effect on coagulation. Conclusion FT4 levels and the FT3/FT4 ratio are crucial prognostic biomarkers in AAD patients. Renal function and coagulation mediate the association between the thyroid hormones and MACEs.